Teens’ Perspective on the Utilization of Public Parks in the City of Gianyar Bali: An Hypothetical Model Based on Grounded Theory - Ni Ketut Agusintadewi; Ade Wisnu Rinartha; Widiastuti . (Pusat Kajian Bali Universitas Udayana, 2022)
Nowadays referred to as the Digital Generation, teenagers tend to be more individualistic and have their own preferences when it comes to spaces for their social interactions. By taking up several cases of public parks in the City of Gianyar, Bali, this study investigated the level of teens’ knowledge about the meaning of city parks with the aim that the results can be a basis for developing a hypothetical model for the utilization of these urban spaces in a more focused and beneficial manner for all users. As a qualitative study employing principles of grounded theory and an exploratory approach, the focus was on data collected from an online questionnaire. Content analysis of this data showed that teens’ knowledge about the city parks is generally quite good. However, their understanding is low about the importance of the utilization of city parks for their social and psychological benefit